Outgassing analysis of the 14-m-long arc-cell vacuum chambers of the Taiwan Photon Source. (December 2016) - Wu, L.H.; Lee, T.Y.; Chang, C.H.; Yang, Y.C.; Huang, C.S.; Huang, Y.T.; Chang, C.C.; Chan, C.K.; Cheng, C.M.; Hsu, S.N.; Hsueh, H.P.; Hsiung, G.Y.; et al.
Abstract: An overall outgassing analysis of the large, 14-m-long, ultra-high-vacuum aluminum arc-cell chambers of the Taiwan Photon Source (TPS) was performed using residual gas analyzer (RGA). Pumping primarily by ion pumps (IP) and non-evaporable getter (NEG) pumps, the cells obtained pressures of 6.4 × 10 −9 Pa on average, and the main residual gas was H2 . The pressure build-up method was adopted to investigate the outgassing of the vacuum chambers. Because active gases (H2, CO, CO2 ) were primarily pumped by NEG pumps, the increased vacuum pressure here mainly resulted from the inert gas. Therefore, the residual gases measured after switched off the ion pumps were CH4 and Ar. After the ion pumps were baked separately, the outgassing of CH4 was considerably diminished and the lowest achievable vacuum pressure was improved. The outgassing of Ar was primarily responsible for the long-term pressure build-up. Moreover, vacuum pressure measurements and residual gas analyses were performed in situ while a cell chamber was being transported. The vibration of the arc-cell vacuum chamber caused the pressure to rise abruptly; in this case, the outgassing gas measured during transportation was CH4 . Once the arc cell was installed, the original level recovered because of the pumping effect of the ion gauges. Highlights: An overall outgassing analysis of vacuum chambers in TPS was studied. The residual gases measured after ion pumps were switched off were CH4 and Ar. After ion pumps were baked, the outgassing of CH4 was considerably diminished. Outgassing of Ar was primarily responsible for the long-term build-up pressure. During transportation, CH4 outgassing related with variation of vacuum pressure.